Effectiveness of Audio-visual Education through Digital Media Platforms Regarding Quality of Life Amongst Breast Cancer Person - Cahyarani, Astika; Solikhah, Solikhah; Djannah, Sitti Nur (Jurnal Promosi Kesehatan Indonesia, 2024)
Background: Improving the education system of patient-centered health information is particularly important for vulnerable populations. The magnitude of the attributable breast cancer burden is very essential to be a concern to developing a good management strategy. Improving the patient’s understanding of their conditions may enhance the quality of life following breast cancer. The study aimed to review the effectiveness of audio-visual education through digital media platforms to improve the quality of life among people with breast cancer.Method: These 1643 articles from eight databases i.e., Scopus, PubMed, MEDLINE via EBSCO, the Cochran Library, Springer Link, Wiley Online Library, BioMed Central, and Sage Journals were searched by a combination of medical subject heading (MESH) term, and unique references were examined. All studies evaluating audio-visual education of women with breast cancer delivered by digital media platforms were included.Results: The search yielded 14 articles with various digital media platforms, such as web-based, applications, e-mail, videoconference, YouTube, and WhatsApp. All studies reported improving quality of life, except one study using WhatsApp as the platform. Audio-visual interventions were variably effective in enhancing the quality of life of patients depending on their characteristics. Audio-visual interventions appear to be effective in improving quality of life amongst breast cancer person. Nevertheless, its effectiveness depends on the frequency and intensity of audio-visual delivery. Meanwhile, the contents of education materials must be adjusted to the administration method. Audio-visual modeling via digital platforms may facilitate improving quality of life and can be an important consideration in future health-education interventions.